Colonoscopy Screening Recommended as Earlier or Better an Investigation of Choice for Colorectal Symptoms - Mandal, Prodip Kumar; Chowdhury, Fayem; Alam, Ishtiaq; Ahsan, Md Kamrul; Masud, AKM Al (Sir Salimullah Medical College Journal, 2022)
Background: Colonoscopic techniques have expanded the role of colonoscopy beyond conventional screening, surveillance, and diagnosis to various complex therapeutic and interventional utilities in colorectal diseases. Objective : (i) To determine the incidence of colorectal cancer in early and late onset. (ii) To determine the incidence in age cohort (iii) To compare clinico-epidemiological features in early and late onset (iv) To bring forth any discrepancies. Methods: It was prospective study conducted in Department of Colorectal Surgery, Bangabandhu Sheikh Mujib Medical University (BSMMU), and Sir Salimullah Medical College Mitford Hospital, Dhaka total 200 cases were included in this study during the period January 2017 to June 2019. Results : Study shows out of 200 respondent 0.5% were under 31-40 years age, 4.5% were between 41-50, and 5.5% were above 50 years. Out of 200 respondent 8% were male in malignancy and 17.5% are benign and 3% were female in malignancy and 14% are benign. Male female ratio was 1.7:1 in malignancy. The most common clinical presentation were per-rectal bleeding (64%), then anaemia/weakness (46%), alteration of bowel habit (36%), pain (10.5%) and obstruction (3.5%). Conclusion: It concluded that proper equipment (colonoscope) and educated personnel, we can introduce colonoscopy as the mandatory screening method of examination, particularly for vulnerable groups. Sir Salimullah Med Coll J 2021; 29(2): 132-135